Vitreous haemorrhage in massive hemorrhagic polypoidal choroidal vasculopathy: clinical characteristics and surgical outcomes. Issue 1 (December 2015) - Narayanan, Raja; Mithal, Kopal; Jalali, Subhadra; Chhablani, Jay; Mathai, Annie; Ali, Md
Abstract Background To report the outcomes of vitreous hemorrhage (VH) associated with hemorrhagic polypoidal choroidal vasculopathy (PCV). Methods A retrospective study of 28 eyes of 27 consecutive patients of hemorrhagic PCV with VH, which were managed surgically between January 2003 and December 2011, was performed. All patients underwent pars plana vitrectomy for VH associated with PCV. The main outcome measure was best-corrected visual acuity (BCVA) at baseline, at 1, 3 and 6 months post operatively and at last follow up. Results The visual acuity measured on early treatment diabetic retinopathy study (ETDRS) chart improved in 16 eyes (57.1 %) by two or more lines, remained unchanged in nine eyes (32.1 %) and decreased in three (10.7 %) after surgery when compared to baseline VA. The mean baseline VA was 2.69 ± 0.57 logMAR units (<20/2000) which improved to 1.65 ± 0.93 logMAR units (20/800) at 1 month post operative visit and was sustained at 1.72 ± 1.12 (20/800) with an improvement of 0.96 logMAR units (p < 0.001, 95 % CI 0.54–1.37). The average postoperative follow up was for 14.2 months (range 1–84). The complications noted in postoperative follow up were cataract (n = 10), macular scaring (n = 9), organised dehemoglobinised blood (n = 7), retinal tear or detachment (n = 5), recurrent VH (n = 3) and choroidal detachment (n = 1). Conclusion Majority of patients with loss of vision due to VH secondary to hemorrhagic PCV have sustained improvement in visual acuity following surgery.